Development of a Plasmid Shuttle Vector System for Genetic Manipulation of Chlamydia psittaci - Kensuke Shima (American Society for Microbiology, 2020)
ABSTRACT The obligate intracellular bacterium Chlamydia psittaci is a known avian pathogen causing psittacosis in birds and is capable of zoonotic transmission. In human pulmonary infections, C. psittaci can cause pneumonia associated with significant mortality if inadequately diagnosed and treated. Although intracellular C. psittaci manipulates host cell organelles for its replication and survival, it has been difficult to demonstrate host-pathogen interactions in C. psittaci infection due to the lack of easy-to-handle genetic manipulation tools. Here, we show the genetic transformation of C. psittaci using a plasmid shuttle vector that contains a controllable gene induction system. The 7,553-bp plasmid p01DC12 was prepared from the nonavian C. psittaci strain 01DC12. We constructed the shuttle vector pCps-Tet-mCherry using the full sequence of p01DC12 and the 4,449-bp fragment of Chlamydia trachomatis shuttle vector pBOMB4-Tet-mCherry. pCps-Tet-mCherry includes genes encoding the green fluorescent protein (GFP), mCherry, and ampicillin resistance (AmpR). Target genes can be inserted at a multiple cloning site (MCS). Importantly, these genes can be regulated by a tetracycline-inducible (tet) promoter. Using the pCps-Tet-mCherry plasmid shuttle vector, we show the expression of GFP, as well as the induction of mCherry expression, in C. psittaci strain 02DC15, which belongs to the avian C. psittaci 6BC clade. Furthermore, we demonstrated that pCps-Tet-mCherry was stably retained in C. psittaci transformants. Thus, our C. psittaci plasmid shuttle vector system represents a novel targeted approach that enables the elucidation of host-pathogen interactions. IMPORTANCE Psittacosis, caused by avian C. psittaci, has a major economic impact in the poultry industry worldwide and represents a significant risk for zoonotic transmission to humans. In the past decade, the tools of genetic manipulation have been improved for chlamydial molecular studies. While several genetic tools have been mainly developed in Chlamydia trachomatis, a stable gene-inducible shuttle vector system has not to date been available for C. psittaci. In this study, we adapted a C. trachomatis plasmid shuttle vector system to C. psittaci. We constructed a C. psittaci plasmid backbone shuttle vector called pCps-Tet-mCherry. The construct expresses GFP in C. psittaci. Importantly, exogeneous genes can be inserted at an MCS and are regulated by a tet promoter. The application of the pCps-Tet-mCherry shuttle vector system enables a promising new approach to investigate unknown gene functions of this pathogen.